Happiness and economic growth: does the cross section predict time trends? ; evidence from developing countries - Richard A. Easterlin; Onnicha Sawangfa (Institute for the Study of Labor (IZA), 2009)
Based on point-of-time comparisons of happiness in richer and poorer countries, it is commonly asserted that economic growth will have a significant positive impact on happiness in poorer countries, if not richer. The time trends of subjective well-being (SWB) in 13 developing countries, however, are not significantly related to predictions derived from the cross sectional relation of happiness to GDP per capita. The point-of-time comparison leads to the expectation that the same absolute increase in GDP per capita will have a bigger impact on SWB in a poorer than a richer country. In fact there is no significant relation between actual trends in SWB and those predicted from the cross sectional relationship. Nor is a higher percentage rate of growth in GDP per capita significantly positively associated with a greater improvement in SWB. In the developing countries studied here a greater increase in happiness does not accompany more rapid economic growth. These conclusions hold true for two measures of SWB that are separately analyzed, overall life satisfaction and satisfaction with finances. The two SWB measures themselves, however, typically trend similarly within a country, providing mutually supporting evidence of the trend in well-being.
urn:nbn:de:101:1-2009030229
Keywords: I31; D60; O5; O10; 330; Happiness; economic growth; developing countries; Lebenszufriedenheit; Wirtschaftswachstum; Sozialprodukt; Entwicklungsländer